Environmental and Economic Assessments of Hydrogen Utilization in the Transportation Sector of Iran. Issue 3 (16th March 2022) - Fayazi Rad, Leila; Amini, Mohammad; Ahmadi, Abolfazl; Hoseinzadeh, Siamak
Abstract: The Iranian transportation industry is an energy‐intensive sector with a wide variety of destructive environmental effects. The use of hydrogen is a promising method to reduce CO2 emissions. Methane decomposition is one of the reliable processes to yield hydrogen. In this paper, the levelized cost, technical parameters, and CO2 emissions of each hydrogen production method are determined and discussed. Finally, it is concluded that steam methane reforming is almost a clean and efficient method of hydrogen production. Besides, maximum generated hydrogen values were obtained using the electrolysis process. To be more precise, in this process, the levelized cost of hydrogen production by photovoltaic, wind, and gas‐combined cycle were evaluated . Abstract : The transportation industry worldwide is constantly expanding which leads to increasing greenhouse gas emissions and environmental pollution. The use of hydrogen is a promising way to reduce CO2 emissions. As air pollution is one of the challenges facing Iranian transportation, different hydrogen production methods and related costs are discussed and the most appropriate methods are proposed.